# Question-68515

Question Number 68515 by azizullah last updated on 12/Sep/19
Commented by Prithwish sen last updated on 13/Sep/19
$$\left[\mathrm{z}\left(\mathrm{z}−\mathrm{6}\right)\right]^{\mathrm{2}} =\left[\left(\mathrm{3}+\mathrm{2i}\right)\left(\mathrm{3}+\mathrm{2i}−\mathrm{6}\right)\right]^{\mathrm{2}} =\left[\left(\mathrm{2i}\right)^{\mathrm{2}} −\left(\mathrm{3}\right)^{\mathrm{2}} \right]^{\mathrm{2}} \\$$$$=\left(−\mathrm{13}\right)^{\mathrm{2}} =\mathrm{169} \\$$
Commented by azizullah last updated on 13/Sep/19
$$\mathrm{thanks} \\$$
Answered by Rasheed.Sindhi last updated on 12/Sep/19
$$=\mathrm{z}^{\mathrm{2}} \left(\mathrm{z}^{\mathrm{2}} −\mathrm{12z}+\mathrm{36}\right) \\$$$$=\left(\mathrm{3}+\mathrm{2i}\right)^{\mathrm{2}} \left(\left(\mathrm{3}+\mathrm{2i}\right)^{\mathrm{2}} −\mathrm{12}\left(\mathrm{3}+\mathrm{2i}\right)+\mathrm{36}\right) \\$$$$=\left(\mathrm{9}−\mathrm{4}+\mathrm{12i}\right)\left(\mathrm{9}−\mathrm{4}+\mathrm{12i}−\mathrm{36}−\mathrm{24i}+\mathrm{36}\right) \\$$$$=\left(\mathrm{5}+\mathrm{12i}\right)\left(\mathrm{5}+\mathrm{12i}−\mathrm{24i}\right) \\$$$$=\left(\mathrm{5}+\mathrm{12i}\right)\left(\mathrm{5}−\mathrm{12i}\right) \\$$$$=\left(\mathrm{5}\right)^{\mathrm{2}} −\left(\mathrm{12i}\right)^{\mathrm{2}} \\$$$$=\mathrm{25}+\mathrm{144}=\mathrm{169} \\$$
Commented by azizullah last updated on 13/Sep/19
$$\boldsymbol{\mathrm{sir}}!\:\boldsymbol{\mathrm{thanks}}\:\boldsymbol{\mathrm{of}}\:\boldsymbol{\mathrm{good}}\:\boldsymbol{\mathrm{work}}. \\$$